2017
DOI: 10.1002/cpe.4090
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing and big data: Technologies and applications

Abstract: to cloud computing and big data technologies, applications, and services.Authors of the selected papers were invited to submit an expanded version to this special issue. These papers were reviewed in the same manner as regular submissions to this edition. After rigorous reviews, 7 papers were accepted for publication and are briefly described in the rest of this section. and the results show that the proposed algorithm outperforms 2 other task-scheduling algorithms in cost and throughput. | Mobile and cloud co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Furthermore, recent studies put more emphasis on the role of remote data storage and processing in the Cloud infrastructures. They showed that, as also stated by Digital Communications Inc (DCI), techniques for remotely processing data are required as data have started to be migrated and managed in the cloud, or even will pass, at some point, through the cloud …”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, recent studies put more emphasis on the role of remote data storage and processing in the Cloud infrastructures. They showed that, as also stated by Digital Communications Inc (DCI), techniques for remotely processing data are required as data have started to be migrated and managed in the cloud, or even will pass, at some point, through the cloud …”
Section: Related Workmentioning
confidence: 99%
“…Cloud computing uses virtualization to prepare services for users that different operating systems can be run on one computer based on the virtualization to increase resource efficiency . In cloud computing, we can alter a physical host to multiple virtual hosts using virtualization technology, and this host can be used as a primary computing unit …”
Section: Introductionmentioning
confidence: 99%
“…10,11 In cloud computing, we can alter a physical host to multiple virtual hosts using virtualization technology, and this host can be used as a primary computing unit. 12 On the other hand, the concept of Internet of things (IoT) is connecting various devices through the Internet. 13,14 IoT offers many types of application services in different domains, such as smart substructure, health care facilities, intelligent transportation system, etc.…”
mentioning
confidence: 99%
“…In cloud computing environments, users can use anytime a variety of devices like PCs, laptops, smart phones, and PDAs to access programs, storage, and application‐development platforms using services offered by cloud computing providers. In fact, users can benefit from the high availability, easy scalability, and low costs in using cloud computing resources (ie, software, infrastructure, and platform) . For instance, cloud computing offers a collection of IT services referred to as Software‐as‐a‐Service to allow users remotely performing their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various efforts have been recently dedicated to improve the performances of all services offered by cloud computing environments. However, there are still many issues that need to be tackled, mainly, scalability, availability, security, and privacy . Despite these issues, cloud computing will remain an environment that continues to play a considerable role in many existing and emerging application domains …”
Section: Introductionmentioning
confidence: 99%